Commissive Utterances in the Translation of Holy Quran Chapter Joseph (A Pragmatics Perspective) - Mawadda, Safriani Ulfa, Dr. Maryadi, M. A. (2016)
This research is aiming at 1) to finding the types of commissive utterances in the translation of Holy Quran chapter Joseph 2) to describing the politeness strategies of commissive utterances in the translation of Holy Quran chapter Joseph. In this research, the writer uses a descriptive qualitative as the type of the research. The data source of this study are verses of chapter Joseph containing commissive utterances in English translation of holy Quran. Concerning the techniques of collecting the data, the writer uses documentation by reading about the content of English translation chapter Joseph. The writer found six types of commissive utterances in the translation of Holy quran chapter Joseph Based on Searle classification. There are Promising, warning, Refusing, threatening, Volunteering and Offering the writer found 6 verses of promising(24%), 6 verses of warning (24%), 4 verses of refusing (16%), 4 verses of threatening (16%), 1 verses of volunteering (4%) and 4 verses of offering( 16%). The majority of the types of commissive utterances that the writer found are promising and warning (24%). Then, writer found four kinds of politeness strategies based on theory Brown and Levinson. There are, bald on record, positive politeness, negative politeness and bald off record. The writer found 16 verses using Bald on Record strategy (64%), 5 verses using positive politeness ( 20%), 3 verses using negative politeness(12%) and 1 verse using bald off Record ( 4%). The majority of politeness strategy that the writer found is bald on record (64%).